TERT promoter mutations are associated with longer progression-free and overall survival in patients with BRAF-mutant melanoma receiving BRAF and MEK inhibitor therapy. (January 2022) - Thielmann, Carl M.; Matull, Johanna; Zaremba, Anne; Murali, Rajmohan; Chorti, Eleftheria; Lodde, Georg; Jansen, Philipp; Herbst, Rudolf; Terheyden, Patrick; Utikal, Jochen; Pföhler, Claudia; Ulrich, Jens; et al.
Abstract: Background: Around 50% of cutaneous melanomas harbour therapeutically targetable BRAF V600 mutations. Reliable clinical biomarkers predicting duration of response to BRAF -targeted therapies are still lacking. Recent in vitro studies demonstrated that BRAF-MEK inhibitor therapy response is associated with tumour TERT promoter mutation status. We assessed this potential association in a clinical setting. Methods: The study cohort comprised 232 patients with metastatic or unresectable BRAF V600-mutated melanoma receiving combined BRAF/MEK inhibitor treatment, including a single-centre retrospective discovery cohort ( N = 120) and a prospectively collected multicenter validation cohort ( N = 112). Patients were excluded if they received BRAF or MEK inhibitors in an adjuvant setting, as monotherapy, or in combination with immunotherapy. Kaplan–Meier and univariate/multivariate Cox regression analyses were performed as appropriate. Results: median age at first diagnosis was 54 years (range 16–84 years). The majority of patients were men 147/232 (63.4%). Most tumours harboured TERT promoter mutations (72%, N = 167). A survival advantage was observed in both progression-free survival (PFS) and overall survival (OS) for patients with TERT promoter-mutant versus wild-type tumours in both the discovery cohort (mPFS of 9.6 months [ N = 87] vs 5.0 months [ N = 33]; hazard ratio [HR] = 0.56 [95% confidence interval CI 0.33–0.96] and mOS of 33.6 months vs 15.0 months; HR = 0.47 [95%CI 0.32–0.70]) as well as the validation cohort (mPFS of 7.3 months [ N = 80] vs 5.8 months [ N = 32]; HR = 0.67 [95%CI 0.41–1.10] and mOS of 51.1 months vs 15.0 months; HR = 0.33 [95%CI 0.18–0.63]). In the pooled cohort of TERT promoter-mutant ( N = 167) versus wild-type ( N = 65) tumours, respectively, PFS was 8.9 versus 5.5 months, (HR = 0.62; 95%CI 0.45–0.87; P = 0.004), and OS was 33.6 versus 17.0 months, (HR = 0.51; 95%CI 0.35–0.75, P = 0.0001). Conclusions: In patients with melanoma receiving BRAF/MEK-targeted therapies, TERT promoter mutations are associated with longer survival. If validated in larger studies, TERT promoter mutation status should be included as a predictive biomarker in treatment algorithms for advanced melanoma. Highlights: TERT promoter mutations are associated with prolonged progression-free and overall survival in patients receiving MAPKi therapy. TERT promoter mutations may serve as a biomarker for response to MAPKi ther apy. In BRAF V600 mutant melanoma patients TERT promoter mutation status may be relevant for deciding which therapy to give.